Chinese Association of Ultrasound in Medicine and Engineering, Superficial Organs and Peripheral Vessels Committee Expert Consensus on Selected Common Clinical Issues in Parathyroid Ultrasound (2024 Edition) - Wang, ZhiLi; Luo, BaoMing; Chen, Wen; Zhou, JianQiao; Lin, Xi; Wang, Yan; Zhou, Qi; Bao, LingYun; Chen, Li; Chen, Wei; Cong, ShuZhen; Dong, FengLin; et al. (Ultrasound in medicine & biology, 2025)
Parathyroid ultrasound is widely used in clinical practice and plays a crucial role in the diagnosis and treatment of parathyroid diseases. Nevertheless, ultrasound physicians frequently encounter a number of challenges and doubts in their professional practice. For this reason, Superficial Organs and Peripheral Vessels Committee of Chinese Association of Ultrasound in Medicine and Engineering has formulated the expert consensus on certain common clinical problems of parathyroid ultrasound based on the current research progress and clinical experience, in order to guide the clinical practice. This consensus describes in detail the diagnostic and interventional common problems of parathyroid ultrasound and provides in-depth discussion on related contents.